2010
DOI: 10.1089/jwh.2009.1907
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Pap Smear Testing in Greece

Abstract: The rate of Pap test use is high among women who reside in Greece, although it is possible that this rate is a little overestimated. Specific programs should be developed and implemented that aim to increase awareness of the benefits of regular cervical cancer screening among specific subgroups of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
4
17
0
1
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36] Our study found similar results, with a college education reducing the nonutilization of screening practice. A lack of insurance was also related to nonutilization as other studies have identified, although in this study population, insurability was high (over 90%).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34][35][36] Our study found similar results, with a college education reducing the nonutilization of screening practice. A lack of insurance was also related to nonutilization as other studies have identified, although in this study population, insurability was high (over 90%).…”
Section: Discussionsupporting
confidence: 77%
“…A lack of insurance was also related to nonutilization as other studies have identified, although in this study population, insurability was high (over 90%). 29,[32][33][34][35][36] Another factor is age. In this analysis, as age increases, Pap smear usage decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Simou et al . ) and to the roles and activities of the professionals in primary care. Physicians (Magai et al .…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of research has explored how neighborhoods or area of residence is associated with cancer screening (Bergamini et al, 2007; Luengo et al, 1996; Simou, Maniadakis, Pallis, Foundoulakis, & Kourlaba, 2010; Todorova, Baban, Alexandrova-Karamanova, & Bradley, 2009). Researchers have shown that geographical access to mammography, such as distance to and transportation, increases utilization (Akinyemiju et al, 2012; Eberth et al, 2014; Peipins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%